Pyramidal ownership and company value: Evidence from Polish listed companies - Maria Aluchna; Tomasz Kuszewski (Contemporary Economics, 2021)
This paper examines the effects of pyramidal ownership. Using the sample of 162 non-financial companies listed on the Warsaw Stock Exchange during the period 2010-2014, we verify the relation between the adoption of a pyramidal structure and company value. Specifically, we show that the link between pyramidal ownership and company value is more complex than previously thought addressing the aspect of ownership concentration and dual class shares. Our results indicate that the use of pyramids is associated with a higher value measured by Tobin's Q, supporting the efficient monitoring hypothesis. Contrary to our expectations the combination of pyramidal ownership and dual class shares is correlated with lower Q. Finally, while the adoption of a pyramid by a majority shareholder does not impact firm value, the combination of a pyramid, ownership concentration and dual class shares is associated with higher Q. This finding suggests that the blockholder ownership outweighs the possible cost of excessive disproportionate ownership and that pyramids and dual class shares have different effects on company value.
Keywords: M21; L25; 330; Pyramidal ownership; pyramidal structures; Poland